Venous Thromboembolism in Hospitalized Patients With Active Cancer. (September 2013) - Piazza, Gregory; Rao, Amanda F.; Nguyen, Thanh Nha; Seger, Andrew C.; Hohlfelder, Benjamin; Fanikos, John; Goldhaber, Samuel Z.
Venous thromboembolism (VTE) is a common complication of cancer and chemotherapy. We evaluated the baseline clinical characteristics, thromboprophylaxis patterns, frequency and timing of VTE, and clinical outcomes in 1000 adult hospitalized patients with active cancer. Overall, symptomatic VTE occurred in 5.4% of hospitalized patients with cancer. The VTE occurred in 2.3% of patients with cancer during hospitalization and in 3.4% between hospital discharge and day 90. Few (13.9%) hospitalized patients with cancer received extended duration pharmacological prophylaxis after hospital discharge. Cancer was the most frequent known cause of death in both the groups. In conclusion, VTE was common in hospitalized patients with cancer, especially after discharge. Inhospital death and death between discharge and day 90 were frequent in hospitalized patients with cancer who developed VTE.